Gut microbiota heterogeneity in non-alcoholic fatty liver disease: a narrative review of drivers, mechanisms, and clinical relevance - Guo, Ying; Zhang, Naisi; Pei, Dongmei (Frontiers in Microbiology, 2025)
Non-alcoholic fatty liver disease (NAFLD), a prevalent metabolic disorder, is increasingly recognized as a complex condition influenced by gut microbiota dysbiosis. However, the heterogeneity in findings across studies has hindered the clinical translation of microbiota-based interventions. In this narrative review, we synthesize current evidence on gut microbial alterations in patients with NAFLD, with a focus on the sources of variability that contribute to inconsistent results. We included human studies (2000–2024) that compared gut microbiota profiles between NAFLD patients and healthy controls using 16S rRNA or metagenomic sequencing; key drivers of microbial changes include clinical factors (metabolic comorbidities, disease progression), biological variables (diet, genetics), and methodological biases (sequencing platform differences, diagnostic criteria variability). Emerging evidence highlights the role of non-bacterial components (fungi, viruses) in modulating bacterial communities and disrupting host metabolic pathways, exacerbating hepatic inflammation and lipid accumulation. To overcome current limitations, we propose integrating multi-omics approaches (metagenomics, metabolomics, and proteomics) with a longitudinal study design to capture dynamic microbiota–host interactions. Precision microbiota therapies, including strain-specific probiotics, engineered microbial consortia, and fecal microbiota transplantation tailored to individual dysbiosis profiles, are emerging as promising strategies for targeted interventions. Addressing these challenges is essential to identifying reliable microbial biomarkers and developing personalized strategies for NAFLD prevention and treatment. Future research should harmonize methodologies, validate causal mechanisms, and optimize microbiota-based therapies to bridge experimental findings and clinical application.